A bibliometric analysis of online faculty professional development in higher education - Gao, Yanjun; Wong, Su Luan; Md. Khambari, Mas Nida; Noordin, Nooreen (SpringerOpen, 2022)
Research on online faculty professional development (OFPD) in higher education has increased in recent years. As there is, nevertheless, a scarcity of quantitative investigations on research publications in this area, a bibliometric analysis of 248 publications collected from the Scopus database was conducted. Biblioshiny and VOSviewer software tools were used for descriptive and network analyses. The research results showed that the overall trend of publication in this domain increased steadily at an annual growth rate of 14.11% during the past 25 years. Journal of Asynchronous Learning Network and Computers and Education ranked the highest among journals with regard to publication number and citation number, respectively. With a total of 298 citations to his paper, Peter Shea was ranked the most impactful author while Maria Northcote, with five publications, was the most productive. In terms of geographical location of research activity, America played the leading role, with Asia emerging in this field. The publication entitled “A Research Agenda for Online Teacher Professional Development” by Dede et al. topped the list for both total citations and average yearly citations. As to recent trends, teacher professional development through online teaching was emergent partly due to the outbreak of Covid-19. Pedagogy training, online community building, and facilitating online teachers were the themes that researchers favored. The study will contribute toward better understanding of the existing literary landscape of research on OFPD given the potential of OFPD in enhancing faculty’s effectiveness in their classrooms and over the course of their teaching careers.